Implementation of the CORBA Event Service in Java - Stephens, Paul (Trinity College Dublin. Department of Computer Science, 1998)
The increase need and interest in distributed technology has led to several different types of object orientated middleware. CORBA is being defined by the Object Management Group (OMG) and is the most commonly used middleware today for building distributed applications. One of the fundamental requirements for a distributed system is to communicate event information between objects. The CORBA standard defines a specification of an Event Service that provides a flexible model for asynchronous communication among objects. This thesis describes the CORBA standard briefly and gives a detail account of the Event Service. The CORBA Event Service specification lacks important features required by application domains such as telecommunications and real-time systems. These limitations are described along with the OMG proposals for a Notification Service and Messaging Service that will overcome the various drawbacks. Also described is a comparison of various event models both CORBA and non-CORBA based, that have been developed by commercial companies and academic institutions. This thesis describes the requirements, design and implementation of TCDEvents, a Java implementation of the CORBA Event Service. Finally, the evaluation of TCDEvents is compared with other CORBA and non-CORBA event models.
Keywords: Computer Science